Kehidupan Gelandangan di Jakarta Tahun 1962-1977 - Pratama, Agustian Aditya; Wasino, Wasino (Universitas Negeri Semarang, 2023)
Jakarta in the early 1960s has experienced a fairly large urban development. The lighthouse project launched by President Soekarno in the early 1960s has made the migration of villagers to Jakarta more frequent. The majority of residents who come to Jakarta are poor and lack skills, which allows them to work in many informal sectors in Jakarta such as pedicab drivers, street vendors and even the homeless. The problem in this study discusses the increase in vagrants in Jakarta in 1962-1977, as well as the purpose of this study to find the beginning of the increase in vagrants in Jakarta and the Government's strategy in dealing with vagrants.